2021
DOI: 10.15282/jmes.15.1.2021.06.0606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of friction stir welding parameters on the residual stress distribution of Al-2024-T6 alloy

Abstract: The objective of this study was to investigate the influences of the main parameters of friction stir welding (FSW) on the residual stresses remained in the FSW of Al 2024-T6. The main parameters were tool rotational speed and tool transverse speed. The effect of these parameters on the residual stresses was studied in both finite element simulation and hole drilling strain gauge measurement. The results showed a good agreement between the numerical results and the experimental outcomes. The change in transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Friction stir welding is a solid-state welding technology that uses a rotational tool to join two material pieces together along the welding path. The tool is plunged into the joining region between both the metallic and polymeric sheets, generating heat through friction and severe plastic strain that enables the joining process [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir welding is a solid-state welding technology that uses a rotational tool to join two material pieces together along the welding path. The tool is plunged into the joining region between both the metallic and polymeric sheets, generating heat through friction and severe plastic strain that enables the joining process [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For the UFG weld, the lower strength was caused by the dissolution of the precipitates but also grain coarsening, as an increase in grain size caused a decrease in mechanical strength [ 46 ]. Another factor could influence the strength of the welds, such as residual stress [ 48 , 49 ]. However, this factor was not investigated in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been conducted to investigate the influence of material location with respect to tool rotation on joint properties in FSW/P. The findings suggest that material position, rotational speed, and traverse speed significantly impact plastic flow behaviour, grain structure, and joint quality [33][34][35]. Research conducted by Guo et al [36] on AA 6061-AA 7075 showed that effective material mixing and the highest joint strength was achieved at the highest traverse speed when AA 6061 was positioned on the advancing side (AS) and AA 7075 on the retreating side (RS).…”
Section: Introductionmentioning
confidence: 99%